1995
DOI: 10.1093/bja/75.5.634
|View full text |Cite
|
Sign up to set email alerts
|

Temporal summation during extradural anaesthesia

Abstract: We have investigated in 10 patients the effect of extradural anaesthesia on temporal summation by comparing pain thresholds to single and repeated (five impulses at 2 Hz) electrical stimuli and compared these tests with pinprick and cold stimulation. Bupivacaine 0.5% (20 ml) was injected at L2-3. After extradural anaesthesia the threshold to repeated stimuli was significantly lower than the threshold to single stimuli (P = 0.0007). Nine patients lost cold sensation and 10 patients pinprick sensation. Pain to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
1
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 7 publications
(8 reference statements)
0
29
1
2
Order By: Relevance
“…In a previous investigation, 6 we found that even extradural anaesthesia did not completely block temporal summation of repeated electrical stimuli: pain to repeated stimuli was blocked in only one of 10 patients, and pain thresholds to repeated stimuli were significantly lower than pain thresholds to a single stimulus.…”
Section: Discussionmentioning
confidence: 60%
“…In a previous investigation, 6 we found that even extradural anaesthesia did not completely block temporal summation of repeated electrical stimuli: pain to repeated stimuli was blocked in only one of 10 patients, and pain thresholds to repeated stimuli were significantly lower than pain thresholds to a single stimulus.…”
Section: Discussionmentioning
confidence: 60%
“…Temporal summation is not blocked by 0.5% bupivacaine epidural anesthesia, 12 contrary to spinal anesthesia with plain bupivacaine 0.5% where the pain response to repeated stimulation disappeared at the sural nerve. 13 Our results suggest that epidural anesthesia with alkalinized 2% lidocaine and epinephrine may inhibit temporal summation also.…”
Section: Me Et Th Ho Od Ds Smentioning
confidence: 72%
“…Described first in cats by Sherrington at the beginning of the last century (Sherrington 1910), the NWR has been extensively applied for the study of experimental nociception in laboratory animals (Schouenborg andKalliomaki 1990, Leandri et al 2011) and human beings (Schouenborg and Kalliomaki 1990, Curatolo et al 1995, Andersen et al 2001, Banic et al 2004, Neziri et al 2010, Leandri et al 2011). …”
Section: The Physiology Of the Nociceptive Withdrawal Reflexmentioning
confidence: 99%
“…Transcutaneous electrical stimulation of a limb peripheral nerve is usually applied to evoke the NWR (Willer 1977, Curatolo et al 1995. Electrical stimulation is easy to use and adequate to elicit stable and reproducible reflexes, bypassing the influence of peripheral transduction mechanisms.…”
Section: Eliciting and Recording The Nwr In Horsesmentioning
confidence: 99%
See 1 more Smart Citation